Corak Pemikiran Kalam dalam Naskah Bahjah Al-'Ulum - Alfan Firmanto (Center for Research and Development of Religious Literature and Heritage, Agency for Research and Development and Training, Ministry of Religious Affairs of the Republic of Indonesia, 2013)
Bahjah Bahjah al-‘Ulum is a syarah or interpretation of the kitab As-Samarqandy. As a syarah or interpretation of As-Samarqandy, Bahjah Al-‘Ulum literature could be categorized as the theological books containing of deep discussion on basic concepts of Islamic theology. This textual study endevours to analyse the contents of the Bahjah Al-‘Ulum literature deals with the basic concepts of faith and its theological thoughts. Keywords: Bahjah Al-‘Ulum, the Concept of Faith.